Developing Coaching Mindset and Skills. (December 2021) - Cannon, Mark; Douglas, Susan; Butler, Deborah
As the use of coaching in organizations continues to grow, managers are increasingly expected to coach their subordinates. However, the development of managerial coaching skills has generally not kept up with organizational desires and needs. We offer a role-play methodology with two scenarios for teaching coaching mindset and related skills. The remedial coaching scenario offers an opportunity to practice coaching an employee on a performance issue or problem. The developmental coaching scenario provides an opportunity for the person being coached to choose a topic to further professional development. The role-plays use a trio format, which has the distinctive benefit of actively involving all members of the class. Each participant takes a turn playing each of the roles of coach, employee, and observer. The observer/feedback giver role enables each student to receive personal feedback. The exercise can be conducted in both in-person and online class formats.